FOXO3a expression is associated with lymph node metastasis and poor disease-free survival in triple-negative breast cancer. Issue 9 (27th March 2018) - Rehman, Abdul; Kim, Yeseul; Kim, Hyunsung; Sim, Jongmin; Ahn, Hyein; Chung, Min Sung; Shin, Su-Jin; Jang, Kiseok
Abstract : Aims: Forkhead box O (FOXO) transcription factors, consisting of FOXO1, FOXO3a, FOXO4 and FOXO6, are involved in carcinogenesis and tumour progression. Recent studies have suggested that FOXOs act as tumour suppressors in a variety of human cancers. This study investigated the clinicopathological significance of FOXOs in triple-negative breast cancer (TNBC). Methods: FOXO protein expressions were assessed by immunohistochemistry in 125 TNBC tissues. Correlations between FOXO protein expression and various clinicopathological parameters, including patients' survival, were investigated. MDA-MB-468 cell line was used for in vitro cell proliferation and migration assay. Results: FOXO1 protein expression was not observed in all 125 TNBC tissues. FOXO4 and FOXO6 protein expressions were detected in 11 (8.8%) and 14 (11.2%) TNBC tissues, respectively. Loss of FOXO4 expression was significantly associated with high histological grade (P=0.014, χ 2 test), and TNBCs with positive FOXO6 expression correlated with high grade (P=0.020, χ 2 test). FOXO3a expression was detected in 40 (32%) TNBC cases and correlated with adverse clinicopathological features, such as lymph node metastasis (P=0.021, χ 2 test), perineural invasion (P=0.013, χ 2 test) and higher Ki-67 proliferation index (P=0.048, t-test). Additionally, FOXO3a expression was significantly associated with poor disease-free survival (P=0.015, log-rank test). In the in vitro study, siRNA-mediated FOXO3a knockdown in the MDA-MB-468 cell line inhibited cell proliferation and migration. Conclusion: Among FOXO members, FOXO3a may have a potential role in promoting tumour cell migration and proliferation and may serve as a prognostic biomarker and a potential therapeutic target for TNBC.